To Study the Impact of Sociodemographic Factors on Glycemic Control of Children with Type I Diabetes Mellitus - Ambreen, Sara; Wari, Rehmana; Tariq, Muhammad; Qayyum, Faiza; Tuz Zahra, Fatima; Saadat, Rashiqa (Biological and Clinical Sciences Research Journal, 2025)
Type 1 Diabetes Mellitus (T1DM) is a chronic autoimmune condition characterized by the destruction of insulin-producing beta cells in the pancreas, leading to lifelong dependence on insulin therapy. Objective: This study aims to identify the impact of sociodemographic factors on Glycemic control of children with Type 1 Diabetes Mellitus by using Sociodemographic Information. Methodology: This Cross-sectional Prospective study was conducted at a Diabetic clinic, children’s Hospital, PIMS from 01/12/23 till 30/11/24. Data were collected through Non-probability consecutive sampling. Both inpatient and outpatient participants meeting the inclusion criteria were included in the study. Demographic and clinical data were collected through a structured questionnaire. Results: In comparison to older children (8–12 years), younger children (ages 1–8) showed superior glycemic control (39.6% good control), with a statistically significant difference (p = 0.001). Glycemic control was positively impacted by 98% of caregivers having either adequate or good knowledge about diabetes management. Compared to children with other caregivers, children whose mothers were their primary caregivers demonstrated improved glycemic control. Good BSR monitoring (≥3 times/day) was associated with improved glycemic control, with 49% of patients exhibiting good monitoring adherence (p = 0.001). Clinically, the mean fasting blood glucose was 195 ± 48 mg/dL, post-prandial blood glucose was 285 ± 62 mg/dL, and HbA1c averaged 9.2 ± 2.1%, indicating poor glycemic control. Conclusion: In our study, glycemic control was not significantly predicted by parental education or socioeconomic level; however, enhanced glycemic control was correlated with caregiver understanding of diabetes management. Additionally, it was discovered that maintaining ideal glycemic control required regular blood glucose checks and maternal involvement as the primary caregiver.